2014
DOI: 10.1371/journal.pone.0085553
|View full text |Cite
|
Sign up to set email alerts
|

Background Coloration of Squamous Epithelium in Esophago-Pharyngeal Squamous Cell Carcinoma: What Causes the Color Change?

Abstract: ObjectivesThis study aims to clarify the cause of background coloration in the epithelia between each dilated intra papillary capillary loop in esophago-pharyngeal squamous cell carcinoma.DesignThis is a single center retrospective study including 124 patients with 160 lesions who underwent esophagogastroduodenoscopy in Nagasaki University Hospital from September 2007 to March 2012; a detailed comparison between endoscopic images and pathology was performed. Immunohistological assessment using anti-human hemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(24 reference statements)
2
4
0
Order By: Relevance
“…Minami et al . reported the presence of extravascular Hb components in esophageal squamous cell carcinoma, and further reported that the anti‐Hb Ab‐positive area was perfectly matched to the cancer area, while the surrounding noncancerous epithelium was negative for Hb staining 12 . However, our study showed positive Hb staining within the epithelium despite the noncancerous lesions, which suggests that the Hb component in the esophageal epithelium may not be a cancer‐specific change (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Minami et al . reported the presence of extravascular Hb components in esophageal squamous cell carcinoma, and further reported that the anti‐Hb Ab‐positive area was perfectly matched to the cancer area, while the surrounding noncancerous epithelium was negative for Hb staining 12 . However, our study showed positive Hb staining within the epithelium despite the noncancerous lesions, which suggests that the Hb component in the esophageal epithelium may not be a cancer‐specific change (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Intervascular background coloration will be useful for predicting histology of HGIN and invasive SCC [ 16 , 17 ]. A recent study indicated that intervascular background coloration might be caused by an extravascular component of hemoglobin that is produced within tumor cells [ 23 ]. The other study showed that intervascular background coloration might be related to the thinning of the keratinous layer or the epithelium caused by neoplastic cell proliferation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…for ESCC or HGIN in previous studies (34.3-36.1%), and thinning of the keratinous layer and the thinning of epithelium, and an extravascular component of hemoglobin were reported as significant factors for brownish epithelium in NBI. 26,27 Nonneoplastic regions with such factors may have caused the low PPV in BLI ‡ Six patients, who had both lesions detected and missed by the primary mode, in the LCI group were counted as missed patients as well as detected patients.…”
Section: Discussionmentioning
confidence: 99%